ARRESTED PRE-OLIGODENDROCYTE MATURATION CONTRIBUTES TO MYELINATION FAILURE IN PREMATURE INFANTS - Buser, Joshua R. (2012)
OBJECTIVE: The major form of MRI-defined white matter injury (WMI) comprises diffuse lesions where the burden of small necrotic foci (microscopic necrosis) is poorly defined. We hypothesized that myelination failure associated with diffuse WMI involves an aberrant injury response linked to arrested pre-oligodendrocyte (preOL) maturation in reactive astrocyte-rich lesions. METHODS: A retrospective autopsy series (1983–2000) was selected for cases with diffuse WMI and analyzed relative to prospectively-collected contemporary cases (2003–2010). Controls were age and region-matched to address regional variation in preOL maturation. Successive oligodendrocyte stages were analyzed with lineage-specific markers. Microscopic necrosis was quantified with microglial markers. Axon injury markers defined the burden of axonopathy. Extracellular matrix remodelling was defined by detection of hyaluronic acid (HA), an inhibitor of preOL maturation, and the HA receptor, CD44. RESULTS: In the contemporary case series, diffuse WMI was accompanied by a significant reduction in the burden of microscopic necrosis and axonopathy. Diffuse astrogliosis extended into the lesion surround with elevated HA and astrocyte-expressed CD44. The total population of OL lineage stages was significantly increased in lesions. This increase coincided with significant expansion of the preOL pool. INTERPRETATION: Although these data confirm that microscopic necrosis occurs in contemporary cases, the markedly decreased burden supports that it does not contribute substantially to myelination failure. The primary mechanism of myelination failure involves a disrupted cellular response whereby preOLs fail to differentiate in diffuse astrogliotic lesions. Pre-oligodendrocyte maturation arrest converts chronic WMI to a more immature state related to the burden of astrogliosis.